Video blog as a new channel of socialization of children: the question of the interpretation of the concept //Videoblog como nuevo canal de socialización de los niños: la cuestión de la interpretación del concepto - Abrosimova, Evgenia E. (Revista de la Universidad del Zulia, 2020)
AbstractThe aim of the article is to address the socialization processes of modern children and adolescents, in the context of the characteristics of the information society and the constant presence of the Internet in their lives. A new but emerging phenomenon is emerging, video blogging, which is part of Internet socialization. The main characteristic of this phenomenon is the potential opportunity that children and adolescents have to create an independent video blogging process, which affects the socialization process in general. The empirical data were collected using quantitative and qualitative sociological methods: survey and interview with children. The combination of these methods provides more complete information to understand the problem. The main result of this study is the evidence that around 30% of children and adolescents are not only viewers of videoblogs, they not only consume the information disseminated by this part of the global network, but also become independent authors of videoblogs. The study results reflect the fact that many children's authors try to imitate their favorite video bloggers. Young Internet users perceive the process of creating a video blog as a certain type of creativity.Resumen El objetivo del artículo es abordar los procesos de socialización de los niños y adolescentes modernos, en el contexto de las características de la sociedad de la información y la presencia constante de Internet en sus vidas. Está surgiendo un fenómeno nuevo pero emergente, los blogs de video, que es parte de la socialización en Internet. La característica principal de este fenómeno es la oportunidad potencial que tienen los niños y adolescentes de crear un proceso de videoblogueo independiente, lo que afecta el proceso de socialización en general. Los datos empíricos se recopilaron utilizando métodos sociológicos cuantitativos y cualitativos: encuesta y entrevista a niños. La combinación de estos métodos proporciona información más completa para comprender el problema. El principal resultado de este estudio es la evidencia de que alrededor del 30% de los niños y adolescentes no solo son espectadores de videoblogs, no solo consumen la información difundida por esta parte de la red global, sino que también se convierten en autores independientes de videoblogs. Los resultados del estudio reflejan el hecho de que muchos autores infantiles intentan imitar a sus video bloggers favoritos. Los jóvenes internautas perciben el proceso de creación de un video blog como un cierto tipo de creatividad.